2021
DOI: 10.3748/wjg.v27.i32.5404
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant angiopoietin-like protein 4 attenuates intestinal barrier structure and function injury after ischemia/reperfusion

Abstract: BACKGROUND Intestinal barrier breakdown, a frequent complication of intestinal ischemia-reperfusion (I/R) including dysfunction and the structure changes of the intestine, is characterized by a loss of tight junction and enhanced permeability of the intestinal barrier and increased mortality. To develop effective and novel therapeutics is important for the improvement of outcome of patients with intestinal barrier deterioration. Recombinant human angiopoietin-like protein 4 (rhANGPTL4) is reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, studies have indicated that TIMP1, SOCS3, ANGPTL4, CDO1, and SERPINE1 are closely associated with CIRI (Liang et al, 2021;Nie et al, 2022;Pu et al, 2022;Wang, Lin et al, 2021) and the HIF-1 pathway (Cui et al, 2015;Fujii et al, 2020;Qi et al, 2023;Warnhoff et al, 2024). Consequently, the expressions of these genes in cerebral cortical tissues were analyzed at both the mRNA and protein levels, and the results of qPCR and Western blotting revealed that EP downregulated TIMP1, SOCS3, ANGPTL4, CDO1, and SERPINE1 expressions in MCAO rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have indicated that TIMP1, SOCS3, ANGPTL4, CDO1, and SERPINE1 are closely associated with CIRI (Liang et al, 2021;Nie et al, 2022;Pu et al, 2022;Wang, Lin et al, 2021) and the HIF-1 pathway (Cui et al, 2015;Fujii et al, 2020;Qi et al, 2023;Warnhoff et al, 2024). Consequently, the expressions of these genes in cerebral cortical tissues were analyzed at both the mRNA and protein levels, and the results of qPCR and Western blotting revealed that EP downregulated TIMP1, SOCS3, ANGPTL4, CDO1, and SERPINE1 expressions in MCAO rats.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant ANGPTL4 reduces no-reflow, hemorrhage and infarct size after myocardial infarction in mice and rabbits [102]. It also attenuates intestinal barrier structure and function after ischemia/reperfusion [108]. Interestingly, the traditional Chinese medicine Tongxinluo is also active against myocardial IRI by stimulating the expression of ANGPTL4 [109].…”
Section: Methodsmentioning
confidence: 99%
“…4 Intestinal I/R injury induces the influx of oxygen, which triggers the overproduction of reactive oxygen species (ROS) and inflammatory reactions in the intestinal epithelium, resulting in programmed cell responses such as apoptosis, autophagy, and necroptosis. [5][6][7] These pathological responses disrupt the integrity of the intestinal mucosal barrier, which is maintained by tight junctions (TJs) and intercellular junctions, 8,9 inducing translocation of gut bacteria and endotoxins to proximal tissues or distal organs 10,11 and eventually leading to deleterious complications such as systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndrome. 12,13 These findings highlight the need to identify new therapeutic strategies against intestinal I/R injury.…”
Section: Introductionmentioning
confidence: 99%